Deindustrialization : Its Causes and Implications. (Economic Issues; Economic Issues ;, 1997)
Over the past 25 years, the share of employment accouted for bymanufacturing has fallen dramatically in the world's most advanced economies, a phenomenon widely referred to as "deindustrialization."Many see deindustrialization as widening income inequalities and causinga sharp rise in unemployment. This paper argues that, contrary to popularperception, deindustrialization should not be regarded as alarming, butrather as a natural consequence of continued economic growth within the advanced economies.